Empowering Mothers as an Alternative to Learning Reading and Interpreting Meaning in Me Tribe Students of Elementary School Age - Sastri Br Rajaguk-guk; Zainal Rafli; Fathiaty Murtadho (Eduvest - Journal of Universal Studies, 2025)
This study examines the empowerment strategies of Mee tribe mothers in Papua in teaching reading to primary school-aged children. The study uses the literature review method to analyse the challenges Mee students face in learning to read and identify effective approaches to improve their literacy skills. The results show that Mee students face various barriers, including limited access to education and language differences. Effective learning strategies include the use of syllable card media, game-based methods and the utilisation of educational technology. The involvement of parents, especially mothers, was found to be very important in supporting the development of children's reading skills. Creating a supportive learning environment at home and empowering mothers as educators can be an effective alternative in improving the reading skills of Mee children. This study recommends the development of a special training programme for Mee mothers, the provision of culturally appropriate learning resources, increased access to educational technology and collaboration between various stakeholders in developing a sustainable literacy programme. The implementation of these recommendations is expected to improve the reading skills of primary school-aged Mee students and empower mothers as important partners in their children's learning process.